Experiences of parents whose children participated in a longitudinal follow‐up study. (8th April 2022) - Franke, Nike; Rogers, Jennifer; Wouldes, Trecia; Ward, Kim; Brown, Gavin; Jonas, Monique; Keegan, Peter; Harding, Jane
Abstract: Background: Long‐term follow‐up is necessary to understand the impact of perinatal interventions. Exploring parents' motives and experiences in consenting to their children taking part in longitudinal studies and understanding what outcomes are important to families may enhance participation and mitigate the loss to follow‐up. As existing evidence is largely based on investigators' perspectives using Western samples, the present pilot study explored parents' perspectives in a multicultural New Zealand context. Methods: Data were generated using semi‐structured interviews with parents whose children had participated in a longitudinal study after neonatal recruitment. Parents' experiences of being part of the study were analysed thematically using an inductive approach. Results: Parents ( n = 16) were generally happy with the outcomes measured. Additionally, parents were interested in lifelong goals such as the impact of parental diabetes. We identified three themes: (1) Facilitators: Research participation was aided by motives and parent and research characteristics such as wishing to help others and straightforward recruitment; (2) Barriers: A hesitancy to participate was due to technical and clinical research aspects, participation burden and cultural barriers, such as complex wording, time commitment and nonindigenous research and (3) Benefits: Children and parents experienced advantages such as the opportunity for education. Conclusions: Parents reported positive experiences and described the unexpected benefit of increasing families' health knowledge through participation. Improvements for current follow‐up studies were identified. Different ethnicities reported different experiences and perspectives, which warrants ongoing research, particularly with indigenous research participants. Patient or Public Contribution: No active partnership with parents of patients took place.